1995
DOI: 10.1136/gut.37.5.660
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium paratuberculosis DNA not detected in Crohn's disease tissue by fluorescent polymerase chain reaction.

Abstract: The role of mycobacteria in the aetiology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 17 publications
2
45
1
2
Order By: Relevance
“…paratubercuhsis from patients with CD [10] sparked renewed interest in this organism in relation to CD. However, detection of mycobacterial DNA in CD tissue by amplification using Ihe polymerase chain reaction (PCR) has produced conflicting results [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…paratubercuhsis from patients with CD [10] sparked renewed interest in this organism in relation to CD. However, detection of mycobacterial DNA in CD tissue by amplification using Ihe polymerase chain reaction (PCR) has produced conflicting results [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…4,6,7,9,15,16,19 Other authors have found a variable number of cases, up to 100%, to harbor the organism. 1,3,5,8,[10][11][12][13][14]18 Several reasons may be responsible for the variability in these results.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,8,[10][11][12][13][14] Thus, the finding of MAP DNA in Crohn's disease, including in paraffin-embedded resection specimens, 1,12 still leaves unanswered the question of whether the organism may be environmentally acquired and nonspecifically present. MAP has been cultured from municipal water supplies 11 and pasteurized milk, 25,26 suggesting that it may be ubiquitously present in the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the theories states that the pathogen Mycobacterium avium subspecies paratuberculosis (MAP) is the causative agent for IBD. However, studies based on the detection of MAP by PCR or ELISA in blood samples or biopsies have shown conflicting results (Autschbach et al, 2005;Baksh et al, 2004;Bentley et al, 2008;Clancy et al, 2007;Rowbotham et al, 1995;Wu et al, 1991). More recently, a newly defined E. coli pathovar, adherent-invasive E. coli (AIEC) was found to be highly associated with ileal mucosa of CD patients (Darfeuille-Michaud et al, 2004).…”
Section: The Role Of Gut Bacteria In Immune Homeostasismentioning
confidence: 99%